2018
DOI: 10.21511/imfi.15(3).2018.07
|View full text |Cite
|
Sign up to set email alerts
|

Fintech platforms in SME’s financing: EU experience and ways of their application in Ukraine

Abstract: The main aim of the given research is to develop an appropriate approach for creation of information FinTech platform with the EU standards compliance mainly for SMEs in order to support innovativeness of SMEs, improve their access to finance and simplify different financial processes. The authors defined the main features of FinTech platforms underlining types of FinTech, its participants and the most influential factors. The main trends of FinTech platforms development in the EU countries, such as the level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 8 publications
0
16
0
1
Order By: Relevance
“…The term "fintech" is a portmanteau of "finance" and "technology" (Fortnum, Pollari, Mead, Hughes & Speier, 2017) that has become especially popular in the financial sector (Gai, Qiu & Sun, 2018) as a result of the dramatic transformation that technologies are effecting in the services that financial institutions offer (Ivashchenko et al, 2018). Indeed, fintech services emerge as innovative options that, by availing of the internet and automated data processing (Lee & Shin, 2018) as well as emerging fields such as big data, artificial intelligence, IoT, and cloud computing (Nakashima, 2018), seek to change the way in which financial products have traditionally been offered (Milian, Spinola & De Carvalho, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The term "fintech" is a portmanteau of "finance" and "technology" (Fortnum, Pollari, Mead, Hughes & Speier, 2017) that has become especially popular in the financial sector (Gai, Qiu & Sun, 2018) as a result of the dramatic transformation that technologies are effecting in the services that financial institutions offer (Ivashchenko et al, 2018). Indeed, fintech services emerge as innovative options that, by availing of the internet and automated data processing (Lee & Shin, 2018) as well as emerging fields such as big data, artificial intelligence, IoT, and cloud computing (Nakashima, 2018), seek to change the way in which financial products have traditionally been offered (Milian, Spinola & De Carvalho, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other platforms that can be useful for the MSE sector are electronic payments, which optimize payment processes and create a financial trail for a company, thus making an indisputable contribution to improving credit rating by allowing financial institutions to verify its income flows through records of sales volumes (Hoder et al, 2016). The payment options provided by these platforms include POS terminals, contactless and digital payments, and QR code payments (Ivashchenko et al, 2018). These solutions, unlike traditional forms of payment, constitute personalized services adapted to the needs of customers, minimizing billing procedures through passwords or biometric authentication (Kang, 2018) and even helping to reduce the risk of theft associated with the use of cash (Urday, Morisaki, & Fasanando, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Fintech can be an alternative financing option that can stimulate business activities in Malaysia. In contrast to Sybirianska et al (2018) which shows that the existence of Fintech lending has not been effectively utilized as an alternative to financing MSMEs in Ukraine. Analysis of the Ukrainian tech market found that more than 60 percent of Fintech lending platforms were launched in the past three years, but their usage has not been maximized.…”
Section: Introductionmentioning
confidence: 78%
“…Fintech requires a large amount of personal data [103], so monitoring the platform is also beneficial for consumer protection [74]. On this basis, the level of data security and infrastructure must be continuously developed [41,43,102,117]. Currently, fintech is also required to collaborate with traditional financial institutions such as banks [31,35].…”
Section: Discussionmentioning
confidence: 99%
“…Although the idea of P2P lending is not new, it is a product of fintech that is developing in countries such as the USA, China, and Indonesia [4]. The hope is that this business model can help SMEs and individuals to obtain loan capital [43]. However, many illegal fintech loans have emerged due to fintech practices that rely on user trust [30].…”
Section: Recommendationsmentioning
confidence: 99%